(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
he aim of this work is the stratigraphic revision of the sequences outcropping on the southwestern side of the M. Mia — M. Matajur anticline. This area, until now, was poorly studied from a geological point of view. Norian to Lower Cuisian strata were recognized, With two hiatuses in the Early and Late Cretaceous. Lithological, biostratigraphical and sedimentological characteristics are described related to formations already known from the bibliography ("Dolomia Principale", "Calcare del Dachstein" and "Calcare di Soccher") while two new Mesozoic carbonatic units are defined; ’ ’Calcari della Fornace" (Lower Liassic—Tithonian) and "Calcareniti di Linder" (Berriasian—Albian). Furthermore several new informal units within the clastic Sequences are differentiated: six Maastrichtian units C ’BrecCia di Montefosca", "Marne Rosse di S. Andrea", "Flysch di Paceida", "Calcareniti di Mersino", "Flysch di M. Brieka" and "Calcareniti di M. Tomba"), three Paleocenic units ("Flysch di Calla", "Flysch di Masarolis" and "Megastrato di M. loanaz"), one Paleocenic—Eocenic unit ("Flysch di Canebola").